The effects of Eurycoma longifolia jack root extract on histological parameters of wound healing - Al-bayati, Maryam Riyadh Yaseen; Faisal, Ghasak Ghazi; Abd. Fuaat, Azliana; Ahmad Affandi, Khairunisa (Penerbit University Sultan Zainal Abidin, 2024)
Wound healing involves multiple phases and biological events which are tightly regulated. Eurycoma longifolia Jack has potent activity several potent biological activities that can help in healing of wounds. This study aimed to assess the histological changes of wound healing induced by the topical application of Eurycoma longifolia jack extract hydrogel on wounds. A total of 20 Sprague Dawley rats were grouped into 4 groups, negative control untreated, Hydrocyn® aqua gel, vehicle hydrogel (xanthan), and Eurycoma longifolia Jack (TA) hydrogel. Excisional wound was created in all animals. The gel was applied two time a day starting from wounding day. Granulation tissue samples were collected on day 5 post-wounding and histological sections were stained by H&E for histological observation of the quantity inflammatory cells, fibroblasts, degree of new blood vessel formation, re-epithelialization, and collagen density. TA hydrogel group showed a significantly higher number of fibroblasts and collagen fibre density with P-value ≤ 0.05. It also improved angiogenesis and epithelialization and maintained inflammatory cells at a moderate level. Conclusion: TA hydrogel improved all histological parameters of wound healing.